The Impact of Supermarket Layouts on Female Shopping Behavior: A Spatial Configuration Analysis - Fahmy, Yara (AUC Knowledge Fountain, 2026)
As supermarkets continue to evolve into hybrid spaces for both consumption and social interaction, understanding how spatial design shapes shopper experience has become increasingly essential. This study investigates the impact of supermarket layout—specifically free-flow configuration—on female shopping behavior within the New Cairo context. Recognizing women as primary decision-makers in household purchasing, the research adopts a gender-informed lens to uncover behavioral patterns, navigation preferences, and layout perceptions. Employing a mixed-methods approach, the study integrates macro-scale online surveys (N = 173 female shoppers) with micro-scale data, including behavioral observation and path tracking of 65 female shoppers, post-shopper interviews, and spatial configuration analysis using Visibility Graph Analysis (VGA). Statistical techniques are employed, including ANOVA, cross-tabulation, correlation, and regression, to examine associations between spatial attributes and shopper behavior. A comparison of potential movement versus actual movement highlights how spatial configuration influences shopper flow. Multiple regression analysis identified through vision and visual clustering coefficient as key predictors of shopper movement, collectively explaining 49.6% of the variance (R2 = 0.495). Based on these findings, a predictive model was developed to estimate shopper presence throughout the retail space. The results advance both theoretical understanding of space syntax in retail contexts and provide evidence- based methodologies for retail layout optimization, confirming that spaces with enhanced visibility and integration attract significantly higher shopper traffic. The study concludes with design recommendations to enhance layout legibility, optimize product visibility, and support inclusive retail environments tailored to female shoppers.